2019
DOI: 10.1101/19007096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Havana Syndrome Among Canadian Diplomats: Brain Imaging Reveals Acquired Neurotoxicity

Abstract: BACKGROUND: In late 2016, US diplomats stationed in Havana began presenting with a variety of neurological manifestations that proved difficult to diagnose. Though previous studies suggested a likely association with brain injury, the mechanism of injury, brain regions involved, and etiology remained unknown. METHODS: We conducted a multimodal study examining 26 Canadian diplomats and their family members, the majority of whom presented with symptoms similar to their American counterparts while residing in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 47 publications
6
24
0
Order By: Relevance
“…Given that the symptom complex with which these diplomats presented suggested potential mild traumatic brain injury, 1 a 23-item Symptom Score Questionnaire (SSQ), derived from the symptom evaluation section of the 22 item Sports Concussion Assessment Tool (SCAT), 12 was administered at each visit (Table 1 ). Five additional questions were added to the SSQ: 1) hearing difficulty in the form of tinnitus, 2) sleeping less than usual, 3) sleeping more than usual, 4) anxiety, and 5) numbness or tingling, the latter added given that a toxicologic source 13 , 14 was being considered in the differential diagnosis at the time. Four questions were removed: 1) confusion as it was evaluated elsewhere, 2) neck pain, 3) pressure in head because there was no evidence of physical head injury, and 4) “don’t feel right.”…”
Section: Methodsmentioning
confidence: 99%
“…Given that the symptom complex with which these diplomats presented suggested potential mild traumatic brain injury, 1 a 23-item Symptom Score Questionnaire (SSQ), derived from the symptom evaluation section of the 22 item Sports Concussion Assessment Tool (SCAT), 12 was administered at each visit (Table 1 ). Five additional questions were added to the SSQ: 1) hearing difficulty in the form of tinnitus, 2) sleeping less than usual, 3) sleeping more than usual, 4) anxiety, and 5) numbness or tingling, the latter added given that a toxicologic source 13 , 14 was being considered in the differential diagnosis at the time. Four questions were removed: 1) confusion as it was evaluated elsewhere, 2) neck pain, 3) pressure in head because there was no evidence of physical head injury, and 4) “don’t feel right.”…”
Section: Methodsmentioning
confidence: 99%
“… 3 A similar set of symptoms was later reported by the Canadian diplomats stationed in Havana and their families. 4 A multimodal assessment of clinical and psychological symptoms revealed that the symptoms were similar to those of the American diplomats. The cause for these changes remains unclear and this ambiguity necessitates an investigation into the relationship between neural effects and the symptoms.…”
Section: Introductionmentioning
confidence: 93%
“… 5 In a cohort of 26 Canadian diplomats and their family members, our group has previously reported the evidence of abnormalities in WM (examined using diffusion-weighted MRI, dMRI), blood-brain barrier integrity and brain electrical activity (studied using magnetoencephalography). 4 The studies of US diplomats have highlighted the resemblance of the observed symptoms to the sequela of traumatic brain injury (TBI). 2 , 5 However, to date there is no consensus regarding the cause of the symptoms, and the proposed aetiologies include both those of internal and external origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Victims of the 1995 Tokyo subway sarin attack had decreased brain volume in the insular and temporal cortex, 5 to 6 years following the attack 61 . A recent report on the Havana Syndrome, which suspects OP insecticide exposure, has found BBB leakage in the insular cortex 62 . Both of these studies were conducted using MRI and detected subtle changes.…”
Section: Resultsmentioning
confidence: 99%